PENGARUH SELF-ESTEEM TERHADAP PERILAKU ASERTIF PADA SISWA SMA N 1 KOTO Xl TARUSAN - Anisa Aviva Dila; Silvi Juwita (STKIP Pesisir Selatan, 2026)
This study aims to examine the level of Assertive Behavior and Self-esteem among students of SMA N 1 Koto XI Tarusan and to investigate the influence between these two variables. This research uses a quantitative approach with a stratified random sampling technique. The research subjects consisted of 286 students from SMA N 1 Koto XI Tarusan. The instruments used were the Assertiveness Formative Questionnaire to measure assertive behavior, developed by Amy Gaumer Erickson and Patricia Noonan (2018), and The State Self-esteem Scale to measure self-esteem, developed by Todd F. Heatherton and Janet Polivy (1991). Data analysis was conducted using simple linear regression with the assistance of IBM SPSS version 26. The results of the study indicate that there is a significant positive effect of self-esteem on assertive behavior with a value of B = 0.241, F = 60.604, p = 0.000 (p < 0.05), R = 0.419, and R² = 0.176. This means that self-esteem contributes 17.6% to the variation in assertive behavior among students of SMA N 1 Koto XI Tarusan. The higher the level of self-esteem, the higher the assertive behavior exhibited by students.